Pelatihan Pembuatan E- LKPD Bagi Guru dalam Pemanfaatan Media Pembelajaran Digital Berbasis Stem Menggunakan Canva di MI Al Istiqlal Karawang - Nurina Kurniasari Rahmawati; Fitriyani Fitriyani; Abdul Hakim Ma’ruf (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Digital transformation in education requires teachers to develop the competence to integrate technology and innovative learning approaches into classroom practices. However, a needs analysis at MI Al Istiqlal Karawang revealed that 54% of teachers experienced difficulties in using digital learning media, 56% predominantly relied on conventional teaching methods, and 50% of the available learning media did not optimally support the learning process. This community service program aimed to enhance teachers’ competence in understanding Science, Technology, Engineering, and Mathematics(STEM)-based learning, utilizing Canva, and developing interactive and contextual STEM-based Electronic Student Worksheets (E-LKPD). The program was implemented through needs analysis, socialization, hands-on training, E-LKPD development practice, mentoring, and evaluation. A total of 50 teachers from MI Al Istiqlal Karawang participated in the program. Evaluation was conducted through observation, product assessment, participant responses, and pre-test and post-test measures, with paired analysis conducted for 12 teachers with complete datasets. The results demonstrated an increase in the mean competency score from 22.33 in the pre-test to 28.42 in the post-test, representing an improvement of 6.08 points (27.2%). The paired sample t-test indicated a statistically significant difference between the pre-training and post-training scores (t = 3.562; df = 11; p = 0.004 < 0.05). Improvements were also observed in teachers’ understanding of STEM-based digital learning media, Canva proficiency, E-LKPD development skills, and readiness to implement the developed media in classroom instruction. Furthermore, participants successfully produced STEM-based E-LKPDs for Mathematics, Science, and Pancasila Education. These findings indicate that practice-oriented training combined with mentoring is effective in strengthening teachers’ digital and professional competencies and supporting the transformation toward innovative, interactive, and 21st-century learning.